Hubungan Kadar Pb Dalam Darah Dengan Profil Darah Pada Petugas Operator Stasiun Pengisian Bahan Bakar Umum di Kota Semarang Timur. - Mifbakhuddin, Mifbakhuddin; Wahyuningsih, Nur Endah; Suhartono, Suhartono (Jurnal Kesehatan Lingkungan Indonesia, 2007)
ABSTRACT Background, Lead (Pb) constitutes as main pollutant in the air of the cities besides the pollution of  sulphur dioxide (SO2), suspended particulate matte (SPM)r, nitrogen oxide (NOX ), and carbon monoxide (CO). The impacts of lead (Pb) exposure on  health are kidney disorder, hypertension, anemia, central nerve disorder, behaviourial changes, fertility disorder, miscarriage, child’s IQ decrease, and the disorder  in formation of hemoglobin. Objective, to find out the correlation between the level of lead (Pb) exposure and the blood profile’s of  gas station workers located in the eastern part of  Semarang City. Method, the research used a  cross sectional design with the number of samples were  39 worker. Independent variable was the level of lead content in blood, while the dependent variable was  blood profile and confounding variables were  health history,  intake of energy and  protein , vitamin B12 , folic acid , vitamin C , the habit of drinking tea, drug use, use of self protective device, smoking habit, and alcohol consumption. Results, the average of blood lead  concentration were measured  13,35 µg/dl, the blood profile that including  the level of haemoglobin, leucocyte, hematocrit, erytrocite, MCV, MCH, MCHC, still in normal limits,  variable of blood lead concentration had significant correlation with the level of hemoglobin and the level of hematocrit,  with  OR = 1,388; 95 %  CI=  1,094 – 1,761  for haemoglobin and OR= 1,358 ; 95 %  CI= 1,095 – 1,685  for  hematocrit respectively. Conclusion, the level of  lead content in  blood which is above normal act as  risk factor of decreasing the level of hemoglobin and hematocrit by 1,388 times and 1,58 times respectively, compared with that of normal level of lead content in the blood.  It is recommended that the gas station worker wear the self protective devices (masker) while working in the gas station in  order to reduce the exposure of lead (Pb) from the motor vehicle exhaust and perform regular medical checkup with certain interval (at least once a year). Key words :Blood lead content, blood profile, gas attendants.